Human kin detection. Issue 3 (12th March 2015) - Bressan, Paola; Kramer, Peter
<x xml:space="preserve">Abstract</x> Natural selection has favored the evolution of behaviors that benefit not only one's genes, but also their copies in genetically related individuals. These behaviors include optimal outbreeding (choosing a mate that is neither too closely related, nor too distant), nepotism (helping kin), and spite (hurting non‐kin at a personal cost), and all require some form of kin detection or kin recognition. Yet, kinship cannot be assessed directly; human kin detection relies on heuristic cues that take into account individuals' context (whether they were reared by our mother, or grew up in our home, or were given birth by our spouse), appearance (whether they smell or look like us), and ability to arouse certain feelings (whether we feel emotionally close to them). The uncertainties of kin detection, along with its dependence on social information, create ample opportunities for the evolution of deception and self‐deception. For example, babies carry no unequivocal stamp of their biological father, but across cultures they are passionately claimed to resemble their mother's spouse; to the same effect, 'neutral' observers are greatly influenced by belief in relatedness when judging resemblance between strangers. Still, paternity uncertainty profoundly shapes human relationships, reducing not only the investment contributed by paternal versus maternal kin, but also prosocial behavior between individuals who are related through one or more males rather than females alone. Because of its relevance to racial discrimination and political preferences, the evolutionary pressure to prefer kin to non‐kin has a manifold influence on society at large. WIREs Cogn Sci 2015, 6:299–311. doi: 10.1002/wcs.1347 For further resources related to this article, please visit the WIREs website. Conflict of interest: The authors have declared no conflicts of interest for this article.